Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPS dengan Model Think Pair Share di Kelas IV SD Negeri 58 Lubuk Buaya Kota Padang - mulyani, riska; hamimah, hamimah; amerta, sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research is motivated by low student learning outcomes, the purpose of this study was to describe the improvement of achievement on learning of citizenship education subject by using cooperative type Think Pair Share (TPS) in fourth grade Lubuk Buaya elementary school 58 Padang, the sample of study subjects was teacher and 22 students. The findings of this research showed that cycle I was average 88% on result of planning, cycle II was 96,42%. Observation on teacher’s aspects cycle I was average 79% cycle II was 91,1%. Observation on student’s aspect cycle I was 76% , cycle II was 91,1%. Student’s achievement cycle I was 74,00%, cycle II was 84,71%.